Primary pancreatic lymphoma camouflaged under the umbrella of spectrum of neuroendocrine tumors in somatostatin receptor imaging - Nikita Sampathirao; M Indirani; S Shelley (World Journal of Nuclear Medicine)
Primary pancreatic lymphomas are very rare as compared to other pancreatic neoplasms. However, unlike carcinomas, pancreatic lymphoma is treatable with satisfactory cure rates. Somatostatin receptor (SSTR) positron emission tomography/computed tomography (PET/CT) with 68Ga-DOTANOC is a well-established diagnostic modality in the management of neuroendocrine tumors (NETs). Over the years, it has been evident that any neoplasm with SSTR expression shows increased tracer uptake, lymphoma, being the most prominent one. Herein, we report a case of pancreatic mass, suggested as NET on fine-needle aspiration cytology referred to us for staging. Whole-body 68Ga-DOTANOC PET/CT scan showed a large pancreatic mass with peripancreatic nodes, level I cervical nodes, cardiac, and left testicular masses which were initially thought to be possibly metastatic from pancreatic NET. However, immunohistochemistry (IHC) of the specimen was suggestive of B-cell Non-Hodgkin's Lymphoma. The present case emphasizes that pancreatic lymphoma is one of the potential differentials for pancreatic masses apart from NET on SSTR imaging. Noteworthy is the fact, that IHC plays a poignant role in the evaluation and is a mandatory tool for the management of tumors. Moreover, the whole imaging picture and clinical scenario ought to be given utmost importance for giving an affirmative diagnosis on imaging. SSTR expression in lymphomas may further obviate a remote fact that peptide receptor radionuclide therapy can be considered as an end of the line treatment for refractory lymphomas.